2003
DOI: 10.1038/sj.bjc.6601300
|View full text |Cite
|
Sign up to set email alerts
|

The expression of P-glycoprotein does influence the distribution of novel fluorescent compounds in solid tumour models

Abstract: Solid tumours display a complex drug resistance phenotype that involves inherent and acquired mechanisms. Multicellular resistance is an inherent feature of solid tumours and is known to present significant barriers to drug permeation in tumours. Given this barrier, do acquired resistance mechanisms such as P-glycoprotein (P-gp) contribute significantly to resistance? To address this question, the multicellular tumour spheroid (MCTS) model was used to examine the influence of P-gp on drug distribution in solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 53 publications
(51 reference statements)
1
39
0
Order By: Relevance
“…The fact that spheroids derived from the radial growth phase and vertical growth phase lesions, which are the same size as those from the metastatic lines, are exquisitely sensitive to these inhibitors suggests that there are no issues with either permeability or drug absorbance onto the matrix. In addition, previous studies using fluorescent drug conjugates, such as BOD-IPY-taxol, have shown the rapid (<360 minutes) transport of drugs to the core of the spheroid (22).…”
Section: Discussionmentioning
confidence: 98%
“…The fact that spheroids derived from the radial growth phase and vertical growth phase lesions, which are the same size as those from the metastatic lines, are exquisitely sensitive to these inhibitors suggests that there are no issues with either permeability or drug absorbance onto the matrix. In addition, previous studies using fluorescent drug conjugates, such as BOD-IPY-taxol, have shown the rapid (<360 minutes) transport of drugs to the core of the spheroid (22).…”
Section: Discussionmentioning
confidence: 98%
“…They were grown according to the ATCC's instruction. Multicellular spheroids were prepared by a liquid overlay method (Martin et al 2003). Briefly, the wells were coated with 0.5 ml of 1.5% agarose containing serum-free medium.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…Development of P-gp -mediated drug resistance in tumors is another major barrier for the effectiveness of cancer therapy (Martin et al 2003). It is well demonstrated that after repetitive treatment of cancer cells with chemotherapeutics, increased expression of the P-gp is associated with a phenotype of multidrug resistance (MDR) (Dusek et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion-limited penetration of molecules into the cultures means that as well as producing oxygen and nutrient gradients they can also develop an acidic central region due to lactate accumulation (Walenta et al, 2000) and have been used to study relations between central pH and medium buffering capacity (Acker et al, 1987). They have been grown using a number of cell types including normal and drug resistant variants (Martin et al, 2003) and have been shown to create an extracellular matrix (Glimelius et al, 1988).…”
Section: Modeling Solid Tumorsmentioning
confidence: 99%